2011
DOI: 10.1258/jtt.2011.110513
|View full text |Cite
|
Sign up to set email alerts
|

A review of telephone coaching services for people with long-term conditions

Abstract: In one-to-one telephone coaching, the patient receives regular telephone calls from a health professional. We have reviewed the evidence for one-to-one telephone coaching. Following a literature search we retrieved 41 articles which reported on the development and the efficacy of 34 separate telephone coaching interventions for LTC management. Telephone coaching for LTC management has only occurred in the last ten years, is becoming increasingly prevalent, and is dominated by interventions in North America and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 55 publications
0
36
1
1
Order By: Relevance
“…Health coaches use motivational interviewing techniques that respect patients' autonomy and help them make health choices that fit with their preferences and situation (Rollnick et al, 2002). There is evidence that targeted health coaching can have a beneficial effect on risk factors and health outcomes, leading to lower mortality rates and improvements in health behaviors Hutchison & Breckon, 2011;Neubeck et al, 2009).…”
Section: Intervention Potential Benefitsmentioning
confidence: 99%
“…Health coaches use motivational interviewing techniques that respect patients' autonomy and help them make health choices that fit with their preferences and situation (Rollnick et al, 2002). There is evidence that targeted health coaching can have a beneficial effect on risk factors and health outcomes, leading to lower mortality rates and improvements in health behaviors Hutchison & Breckon, 2011;Neubeck et al, 2009).…”
Section: Intervention Potential Benefitsmentioning
confidence: 99%
“…63,282,415,431,432 These have continued to support our previous conclusion that the evidence for the benefit of telehealth is limited, although a systematic review of telephone health coaching for people with LTCs published in 2011 was generally positive. 433 A useful review focused on the evidence on the implementation as well as the effectiveness of interactive web-based programmes for older patients with LTCs. 413 This found that these programmes were associated with improvements in self-efficacy and self-management behaviours, but there was little evidence of benefits in terms of health outcomes.…”
Section: Data Sharing Statementmentioning
confidence: 99%
“…Cochrane has assembled a sample inventory of such aids [103]. The positive effects of decision aids are increased when combined with face-to-face counseling or targeted coaching [35]. In Coulter and Ellins' review, younger adult patients with multiple complex problems seem to require more direct and longerterm involvement with clinicians [8,24,104].…”
Section: Study (Year) Foci/sr Foci Design/study Population Major Findmentioning
confidence: 99%